2014
DOI: 10.1111/are.12446
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation induction in jundiá (Rhamdia quelen, Heptapteridae) using carp pituitary extract or salmon GnRH analogue combined with dopamine receptor antagonists

Abstract: Jundi a (Rhamdia quelen) is an important species for aquaculture in temperate and subtropical climates. In the present study, the results of different forms of GnRH analogue treatments on ovulation in jundi a have been compared with those from treatment with carp pituitary. Seven out of eight females ovulated in groups treated with carp pituitary (4.0 mg kg À1 BW) and Ovaprim (0.5 mL kg À1 BW). Injection with sGnRHa (10 lg kg À1 BW) combined with metoclopramide (20 mg kg À1 BW) caused a significantly lower rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…In this study we observed that CPE and mGnRHa + MET treatments provoked ovulation in L. friderici, but the lower CPE dose treatment was the unique that provided viable embryos. This pattern of response is unusual mainly because conventional CPE dose (0.5 mg and 5.5 mg/kg, with 12h interval, with some variations) has provided ovulation and viable embryos in many fish species evaluated worldwide (Mylonas et al, 2010) and is the mainly hormonal therapy used for inducing tropical migratory fish ovulation (Caneppele et al, 2015;Souza et al, 2015;Ittzés et al, 2015;Viveiros et al, 2015;Sanches et al, 2016;Pereira et al, 2017;García et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study we observed that CPE and mGnRHa + MET treatments provoked ovulation in L. friderici, but the lower CPE dose treatment was the unique that provided viable embryos. This pattern of response is unusual mainly because conventional CPE dose (0.5 mg and 5.5 mg/kg, with 12h interval, with some variations) has provided ovulation and viable embryos in many fish species evaluated worldwide (Mylonas et al, 2010) and is the mainly hormonal therapy used for inducing tropical migratory fish ovulation (Caneppele et al, 2015;Souza et al, 2015;Ittzés et al, 2015;Viveiros et al, 2015;Sanches et al, 2016;Pereira et al, 2017;García et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Still in this context, the most commonly protocol used for obtaining viable embryos in South American reophilic species is still the use of carp pituitary extract (CPE) in conventional dose (0.5 and 5.0 mg/kg), which is applied in a generalized way in different species (Carneiro and Mikos, 2008;Caneppele et al, 2015;Souza et al, 2015;Ittzés et al, 2015;Viveiros et al, 2015;Schorer et al, 2016;Pereira et al, 2017). However, the main problem related to the use of CPE is a constant uncertainty and unpredictability of a successful ovulation (Criscuolo-Urbinati et al, 2012;Hainfellner et al, 2012a, b;Pereira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Females were randomly submitted to two different hormonal treatments routinely used in fish farms: (1) crude carp pituitary extract (CPE) (Fish braz Ò )-two doses (0.5 and 5.0 mg kg -1 , 12 h interval, diluted in 0.5 mL saline-0.9 % and (2) mammalian analogue gonadotropin-releasing hormone in liquid form (mGnRHa) (conceptal Ò /Intervet)-single dose (7 lg kg -1 , diluted in 10 ml sterile buffered diluent, associated with a dopamine inhibitor (10 mg kg -1 metoclopramide, diluted in 0.5 ml saline-0.9 %) ( Table 1). Selection of the doses of both hormonal inducers was based on previous studies with other rheophilic South American species which showed efficacy in the reproductive process (Criscuolo-Urbinati et al 2012;Ittzés et al 2015).…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…Rheophilic fish are the most important native fish for commercial purposes in South American countries (MPA 2013;FAO 2014). For these species, different from many marine (Rosenfeld et al 2012;Fernández-Palacios et al 2015) and temperate (Szabó et al 2002; Genz et al 2014) fresh water species, the most commonly used technique for obtaining viable embryos in captivity is still the application of carp pituitary extract (CPE) (Caneppele et al 2015;De Souza et al 2015;Ittzés et al 2015;Viveiros et al 2015) because this, at a certain extent, has been practically the only effective technique for this purpose in this species (Leonardo et al 2004;Felizardo et al 2012;Santos et al 2013). On the other hand, the main problem related to the use of CPE is a constant uncertainty and unpredictability of a successful ovulation (Criscuolo-Urbinati et al 2012;Hainfellner et al 2012a, b).…”
Section: Introductionmentioning
confidence: 99%